Empowering Groups of Farmer Exposed to Pesticides Pollution in Jembrana District - Ratna Juwita (WMJ (Warmadewa Medical Journal), 2019)
Pesticides are chemicals that are regularly used by farmers to manage pests. The adverse effects of pesticides affect not only pests but also farmers working without proper and correct personal protective equipment (PPE). The Eastern (Kangin) and Western (Kauh) groups of local farmer association, called the Tegal Wani Subak, in the Jembrana sub-district are farmer the groups that use pesticides regularly. Several health symptoms related to pesticides/ organophosphates exposure such as skin redness, eye irritation, dry throat and dizziness have frequently occurred. Based on field observation and discussion with participants, none of the farmers completely equipped with PPE and the farmers was exposed to pesticides contamination. Occupational Health and Safety (OHS) induction program was conducted to increase awareness, knowledge and practices of the farmers on the hazards of pesticides, early detection of pesticide poisoning and preventive interventions based on OHS approach. This program was an interventional study with a pre-post test approach which was participated by seven farmers and evaluated for one month. The pre-test results showed an improvement in the participants’ knowledge from 28.7 %, to 84.3 %. The general results of Focused Group Discussion (FGD) revealed that participants had a good understanding of pesticides; however, the understanding of PPE remained low. Weekly observations and assessments showed that the use of PPE had increased by 100%, except for boots use (71% ); all health symptoms decreased to 0%, except those related to nervous systems which actually increased from 71% to 76% (45% reported of hyperhydration/hypersalivation and 71% reported of headaches). The sustainable and active involvement of OHS officers in primary health centre (Puskesmas) is very important to overcome the problem of organophosphate use in a wider population of farmers.